A Review on Travelling Assistance Smart Wearables for the Visually Impaired (Journal of Fiber Bioengineering and Informatics, 2025)
Difficulty in travelling has always been a problem for visually impaired people in their daily lives, andsmart wearable devices have shown great potential in helping the visually impaired to travel by theirportability and interactivity. Therefore, this paper provides an overview of smart wearable devicesthat assist the visually impaired in travelling. The paper first analyses the characteristics of visuallyimpaired people to understand their needs, and then briefly reviews the history of travel assistancedevices. The paper then analyses the working mechanisms of smart wearable devices and divides theminto three categories based on how they return information to the user. Then, the paper summarises theadvantages and disadvantages of different types of devices and the disadvantages common to all types bydetailing the working principles, functions, and usage effects of a dozen different types of devices. Finally,it summarises the current research status and limitations, and proposes future research directions. Itaims to provide a reference for the development of smart wearable devices that assist visually impairedpeople in travelling.
Keywords: Visually Impaired People; Smart Wearable; Travel Aids; Information Feedback.